2021
DOI: 10.1017/pds.2021.93
|View full text |Cite
|
Sign up to set email alerts
|

Derivation of Motivators for the Use of Aluminum Foam Sandwich and Advantageous Applications

Abstract: Aluminum foam sandwich (AFS) is an innovative material combination for designing lighter products and has many advantages such as a high bending stiffness at a low density and good energy absorption properties. Although the material is ready for series production, the number of industrial applications is low because of the high costs of the material, a lack of design knowledge and missing reference applications. This paper focuses on the aspect of missing reference applications and how to improve this situatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…A systematic literature review by Hommel et al (2021) served to investigate where AFS has been used or could be used and which advantages arise from the use of AFS. These results were then used to develop a set of motivators for the use of AFS, which will support the designer in evaluating its potential use.…”
Section: Motivators For the Use Of Aluminum Foam Sandwichmentioning
confidence: 99%
See 2 more Smart Citations
“…A systematic literature review by Hommel et al (2021) served to investigate where AFS has been used or could be used and which advantages arise from the use of AFS. These results were then used to develop a set of motivators for the use of AFS, which will support the designer in evaluating its potential use.…”
Section: Motivators For the Use Of Aluminum Foam Sandwichmentioning
confidence: 99%
“…The characteristic powder metallurgical manufacturing process creates a metallic bond between the face sheets and the core; as this does not require any adhesives, it therefore has a high recycling quality (Seeliger, 2011). Because of its many advantages, such as high bending stiffness at low density, good damping behavior and beneficial mechanical energy absorption, AFS has a wide range of possible applications (Banhart et al, 2019;Hommel et al, 2021;Sviridov, 2011). Components made of AFS can prove particularly Aluminum foam core Aluminum face sheets profitable in mechanical and plant engineering, for example in load-bearing structures within machine tools (Hipke et al, 2007), and in the automotive industry, such as in battery boxes for electric vehicles or crash-relevant components (Banhart et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to this characteristic manufacturing process, no adhesive is necessary, which means AFS has a high recyclability. Thanks to the other advantages of AFS, such as low density, high specific bending stiffness, and good damping properties, this material can be used for a wide range of different applications (Banhart et al, 2019;Drossel et al, 2018;Hommel et al, 2021a). These particularly include crash-relevant components (Banhart et al, 2019), where the high energy absorption capacity of AFS is advantageous, as well as moving components in machine tools (Hohlfeld et al, 2018) and in general transport vehicles (Viehweger and Sviridov, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Aluminium foam sandwich panels (AFS) have been evaluated for many applications, such as an Ariane 5 rocket adaptor [18], solar thermal energy generation, cooking equipment, architectural panels, and blast and bullet protection [19]. Hommel et al [20] tried to identify profitable applications for the AFS and developed a set of motivators for the use of the aluminium foam sandwich. A survey revealed that potential users of AFS need design support and recommendations on how to design with these relatively new materials [21].…”
Section: Introductionmentioning
confidence: 99%